Comparison of Safety Profile of Delafloxacin (DLX) vs. Vancomycin/Aztreonam (VAN/AZ) in theTreatment of Patients with Acute Bacterial Skin and Skin Structure Infections (ABSSSI): Integrated Safety Findings from Two Phase III Studies. (4th October 2017) - Corey, G Ralph; Hooper, David; P. Lodise, Thomas; Tseng, Carol; Cammarata, Sue K
Abstract: Background: DLX is an investigational novel fluoroquinolone in development for the treatment of adult patients with ABSSSI. The objective of this analysis was to compare the incidence of adverse events between DLX and VAN/AZ across two phase III registrational ABSSSI studies. Methods: Study design and population: two global multi-center, double-blind randomized Phase 3 trials of adults with ABSSSI who receive either DLX IV/oral monotherapy q12h or VAN 15mg/kg with AZ q12H for 5 – 14 days. Collected safety data included all reported AEs (baseline to 30 days after the final dose of study drug). Adverse events were reported by the blinded investigator who also assessed whether the reported events were potentially related to the treatment. Pre-specified laboratory tests were also collected from baseline through day 21–28. Results: Across the 2 studies, 1492 ABSSSI patients received at least one dose of treatment. Mean age was 49 years; 13% >age 65. Among the 1492 patients, 42% were obese, 11% were diabetic, and 16% had renal impairment. Overall, rates of any AE were comparable between treatment groups (table). The most common AEs were gastrointestinal, seen in 17% and 13% of DLX and VAN/AZ patients, respectively. Less than <1% of DLX patients discontinued treatment due to related AEs. For DLX and VAN/AZ, there were 1.1% and 1.7% patients with ALT>5X ULN at any time in the study. There was one case of C. difficile infection on DLX in a patient with prior Bactrim/clindamycin therapy. There was no increase in events previously associated with FQs compared with VAN/AZ. There were no cases of tendon rupture or reports of patients with symptoms consistent with FQAD. Conclusion: Overall, the safety profile of DLX was comparable to VAN/AZ among patients with ABSSSI. Disclosures: G. R. Corey, Melinta: Consultant, Consulting fee; D. Hooper, Melinta: Consultant, Consulting fee; T. P. Lodise Jr., Melinta: Consultant, Consulting fee; C. Tseng, Melinta: Consultant and Research Contractor, Consulting fee; S. K. Cammarata, Melinta Therapeutics: Employee, Salary